Glutamine as an Essential Amino Acid for KRas-Driven Cancer Cells. (June 2019) - Bernfeld, Elyssa; Foster, David A.
Abstract : Cancer cells consume glutamine, a nonessential amino acid (NEAA), at exceedingly high rates to fulfill their energetic and biosynthetic requirements for proliferation. Glutamine plays distinct roles from essential amino acids in cell cycle progression and in the activation of mammalian target of rapamycin (mTOR). Furthermore, the need of cancer cells for glutamine can be exploited therapeutically – especially those driven by KRas. In this review we explore several distinct cellular roles for glutamine that contribute to glutamine addiction in KRas-driven cancer cells and discuss opportunities for therapeutic intervention created by glutamine addiction. Highlights: Glutamine activates mTORC1 by leucine-dependent and leucine-independent mechanisms. There is a late-G1 glutamine-dependent checkpoint that is dysregulated in KRas-driven cancer cells. Blocking glutamine utilization in KRas-driven cancer cells causes S-phase arrest and sensitizes to rapamycin. Aspartate generated by the glutamate-oxaloacetate transamination reaction promotes nucleotide biosynthesis and redox balance.